2011
DOI: 10.1074/jbc.m110.195305
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Metabolic Effects of Adaptive Glycerol Kinase (GLPK) Mutants in Escherichia coli

Abstract: Herein we measure the effect of four adaptive non-synonymous mutations to the glycerol kinase (glpK) gene on catalytic function and regulation, to identify changes that correlate to increased fitness in glycerol media. The mutations significantly reduce affinity for the allosteric inhibitor fructose-1,6-bisphosphate (FBP) and formation of the tetramer, which are structurally related, in a manner that correlates inversely with imparted fitness during growth on glycerol, which strongly suggests that these enzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 70 publications
8
55
0
Order By: Relevance
“…3c). A previous study showed reduced intracellular cAMP level in the GLPK strain, and this result was consistent in three other knock-in strains with different adaptive glpK mutations 10 . This observation is further supported at the proteome level by a twofold decrease of cAMP receptor protein (Crp) in GLPK and DKI strains ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…3c). A previous study showed reduced intracellular cAMP level in the GLPK strain, and this result was consistent in three other knock-in strains with different adaptive glpK mutations 10 . This observation is further supported at the proteome level by a twofold decrease of cAMP receptor protein (Crp) in GLPK and DKI strains ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 56%
“…Since cAMP-Crp activates tricarboxylic acid (TCA) cycle genes, acetate formation ARTICLE NATURE COMMUNICATIONS | DOI: 10.1038/ncomms4233 is limited on glycerol, a normally non-fermentable carbon source. On the other hand, the glycerol uptake rate was enhanced in the glpK mutant most probably because of reduced inhibitory effect of fructose 1,6-bisphosphate on GlpK, as shown previously for this mutant 10 . This results in increased transfer of phosphate from phosphorylated EIIA Glc to produce glycerol-3-phosphate 28 .…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations